Control of xylem Na+ loading and transport to the shoot in rice and barley as a determinant of differential salinity stress tolerance - Ishikawa, Tetsuya; Shabala, Sergey (Physiologia plantarum, 2019)
Control of xylem Na+ loading has often been named as the essential component of salinity tolerance mechanism. However, it is less clear to what extent the difference in this trait may determine differential salinity tolerance between species. In this study, barley (Hordeum vulgare L. cv. CM72) and rice (Oryza sativa L. cv. Dongjin) plants were grown under two levels of salinity. Na+ and K+ concentrations in the xylem sap, and shoot and root tissues were measured at different time points after stress onset. Salt‐exposed rice plants prevented xylem Na+ loading for several days, but failed to control this process in the longer term, ultimately resulting in a massive Na+ shoot loading. Barley plants quickly increased xylem Na+ concentration and its delivery to the shoot (most likely for the purpose of osmotic adjustment) but were able to reduce this process later on, keeping most of accumulated Na+ in the root, thus maintaining non‐toxic shoot Na+ level. Rice plants increased shoot K+ concentration, while barley plants maintained higher root K+ concentration. Control of xylem Na+ loading is remarkably different between rice and barley; this difference may differentiate the extent of the salinity tolerance between species. This trait should be investigated in more detail to be used in the breeding programs aimed to improve salinity tolerance in crops.